2009
DOI: 10.1007/s11243-008-9181-9
|View full text |Cite
|
Sign up to set email alerts
|

Mixed chromium(III) complexes with pyridinedicarboxylato and oxalato ligands: kinetic studies in HClO4 solutions

Abstract: Three chromium(III) complexes of general formula [Cr(ox) 2 (pdaH)] 2-(where ox = C 2 O 4 2-and pdaH -is N,O-bonded 2,3-, 2,4-or 2,5-pyridinedicarboxylic acid anion) were obtained and characterized in solution. Acid-catalysed aquation of [Cr(ox) 2 (pdaH)] 2-gave two products: [Cr(ox)(pdaH)(H 2 O) 2 ] 0 (P 1 ) and cis-[Cr(ox) 2 (H 2 O) 2 ] 2-(P 2 ). The kinetics of these reactions were studied spectrophotometrically, within the 0.1-1.0 M HClO 4 range, and the pseudo-first-order rate constants for the oxalato (k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 21 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Previously, series of complexes with pyridinemonocarboxylato and pyridinedicarboxylato ligands were obtained and kinetic studies on their acid-and base-catalysed aquation were performed [e.g. [6][7][8][9][10]. Additional studies on their effect toward 3T3 fibroblasts revealed that they are not toxic and may be good candidates as biochromium sources [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, series of complexes with pyridinemonocarboxylato and pyridinedicarboxylato ligands were obtained and kinetic studies on their acid-and base-catalysed aquation were performed [e.g. [6][7][8][9][10]. Additional studies on their effect toward 3T3 fibroblasts revealed that they are not toxic and may be good candidates as biochromium sources [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the hydroxyl anion in the inner sphere destabilises the bidentate bonded oxalato ligand regardless of the fact that quin is already one-end bonded. Our studies on acid-catalysed aquation of complexes with picolinato-like ligands, showed that the chelate-ring opening takes place at the Cr-N bond [7,[17][18][19] and produces a relatively inert aqua-form intermediate stabilised by the intramolecular hydrogen bond between pyridine nitrogen and 2-carboxylate oxygen atoms. This process is reversible, and the amount of the intermediate decreases with an increase in pH.…”
Section: Resultsmentioning
confidence: 87%
“…Further processes obscure, to some extent, the spectroscopic scans registered after the fast period and the results obtained are mainly of qualitative importance. Comparison of the results obtained for the acid [19] and base hydrolysis led to the establishment of the pH effect on the complex reactivities. However, because in acidic media the parallel ligands dissociation (at ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations